The presence, characteristics and correlates of pathological social withdrawal in Taiwan: An online survey. (February 2020) - Wu, Alison Fang-Wei; Catmur, Caroline; Wong, Paul WC; Lau, Jennifer YF
Objectives: Pathological social withdrawal (PSW) has become a public health concern, especially in Asia. However, few studies have investigated the presence of PSW and its characteristics in Taiwan. In this study, we aimed to discover whether individuals in Taiwan display PSW behaviours, the demographic characteristics and psychiatric history of those meeting criteria for PSW and the associated psychological risks. Methods: An online self-report survey collected participants' demographic characteristics, social behaviours and their psychiatric history, along with information on adherence to cultural norms and mental health. Results: Among 1, 046 valid respondents, 9% reported behaviours consistent with PSW for at least 6 months, commensurate with other online surveys in Asian countries. Around 20% of these also reported current or past psychiatric disorders, although this was lower than previous findings (50%–80%). Participants with PSW reported poorer mental health and lower confidence in social/academic/work skills than unaffected participants. Conclusion: This study identified for the first time the presence of PSW in Taiwan. Except the lower rates of psychiatric comorbidity (which could be explained by sociocultural factors and sampling methods), data were consistent with previous findings. We also extended our understanding of possible psychological risk factors associated with this pathological condition.